2011 IEEE 12th International Workshop on Signal Processing Advances in Wireless Communications 2011
DOI: 10.1109/spawc.2011.5990422
|View full text |Cite
|
Sign up to set email alerts
|

Closed-form blind channel estimation in orthogonally coded MIMO-OFDM systems: A simple strategy to resolve non-scalar ambiguities

Abstract: We consider blind channel estimation in multiple-input multipleoutput orthogonal frequency-division multiplexing (MIMO-OFDM) systems with orthogonal space-time block code (OSTBC). We introduce a novel weighted covariance matrix of the received data which exploits all redundancies contained in the code. Based on the orthogonality properties of OSTBCs, we further show that a low-rank subspace mode applies to this matrix. Assuming a delay spread over the wireless channel smaller than the OFDM symbol duration, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Our work is not the same as this work as we in light of altered ICA way to deal with blind interference cancellations and error minimization. In [9], another blind channel estimation technique in the MIMO-OFDM system with the equilateral spacetime piece code investigated. This approach composed the new weighted covariance matrix of data recognize in the direction to obtain the errors in the code.…”
Section: Related Workmentioning
confidence: 99%
“…Our work is not the same as this work as we in light of altered ICA way to deal with blind interference cancellations and error minimization. In [9], another blind channel estimation technique in the MIMO-OFDM system with the equilateral spacetime piece code investigated. This approach composed the new weighted covariance matrix of data recognize in the direction to obtain the errors in the code.…”
Section: Related Workmentioning
confidence: 99%
“…Then, the covariance matrix of the obtained virtual snapshots in (11) for the ith subcarrier can be defined as [4] Xi E{…”
Section: B Blind Channel Estimationmentioning
confidence: 99%
“…It can be shown that the true channel vector hi corresponding to the ith subcarrier is the principal eigenvector (or one of the principal eigenvectors in the case of multiplicity) of the matrix Xi [11], hence,…”
Section: B Blind Channel Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Sarmadi et al in [10] proposed a semi-definite relaxation technique to achieve blind channel estimation for orthogonal STBC-OFDM systems. Another method was also proposed in [11]. It is based on the weighted covariance approach which explores all redundancies contained in the orthogonal code to resolve channel estimation non-scalar ambiguities.…”
Section: Introductionmentioning
confidence: 99%